University extension: setting and funding (Research, Society and Development, 2020)
The present study aims to critically analyze the role of the CLAC / UFRJ project, verifying its compliance with the institutional extension guidelines. This is an analytical study, using a bibliographic method. The study started from the following question: given the specificity of public Universities, therefore, free, how do you explain charging for a course offered? Furthermore, why does extension, as a rule, occupy the last position in order of priority and importance? The study concluded that in relation to the order of priority, this is explained because research is more easily funded by the various agencies that promote research; teaching is explained by its own primary condition and target of institutions for this purpose. As for charging, in the case of the studied project, it is justified, according to previously published studies, the managers claim that it is due to the fact that the funds destined to Universities are not sufficient to finance extension projects efficiently, being necessary, therefore, the collection of the fee, however, noting that the fee is symbolic and much lower compared to the monthly fees charged in the private sphere in similar courses. He also concluded that the project satisfactorily fulfills its role of integrating university and community, even though it is not yet in ideal conditions, and recommending future empirical studies involving students, in order to verify their opinion in relation to the project.